A Functional Assay to Assess Toxicity During Murine B Cell Development In Vitro. Issue 1 (18th December 2019) - Guilbert, Cynthia; Chou, Hsiang; Bolt, Alicia M.; Wu, Ting Hua; Luo, Vincent Mingyi; Orthwein, Alexandre; Mann, Koren K.
Abstract: B lymphocytes, or B cells, are important players in immunity that produce antigen‐specific immunoglobulins. As a result, they are involved in various immune‐linked pathologies. To better understand, prevent, or treat B cell–associated disease and immunotoxicity, we developed an in vitro assay to model early murine B cell differentiation within the bone marrow. This model uses sorted B cell precursors cultured on a supporting stromal cell layer, which over time acquire markers of further differentiated B cells, such as surface antigens and rearranged immunoglobulin light chain. Importantly, we utilized our in vitro model to validate our previous observations that xenobiotics, such as tungsten and organotins, alter B cell development in vivo. Furthermore, gene expression can be modulated in this model using retroviral transduction, making it amenable to investigating signaling pathways involved in disruption of B cell differentiation. © 2019 by John Wiley & Sons, Inc. Basic Protocol : Assessment of early B lymphocyte differentiation in vitro Support Protocol : Isolation of murine bone marrow Alternate Protocol 1 : Addition of recombinant interleukin‐7 Alternate Protocol 2 : Genetic manipulation via retroviral transduction